Pengaruh Literasi Keuangan Syariah dan Perilaku Konsumtif terhadap Minat Jasa Pinjaman Online - Sintawati, Dewi; Nizar, Muhammad; Fahmul Iltiham, Muhammad; Farida, Alimatuf (Journal of Islamic Economics Studies and Practices, 2023)
This study examines the effect of Islamic financial literacy and consumptive behavior on interest in online loan services at Yudharta University, Pasuruan. This research uses a quantitative approach with a descriptive research type. Data collection techniques through distributing questionnaires using the Google form. Data analysis using multiple linear regression. The results of the research in this study indicate that Islamic financial literacy and consumptive behavior affect interest in online loan services.